The Effect of Using Suggestopedia Method on Reading Comprehension in Descriptive Text at Tenth Grade of SMA N 8 Kota Jambi - Sulastri Lisnawati; Suyadi Suyadi (JELT: Journal of English Language Teaching, 2020)
This research was done to find the effect of using suggestopedia method on reading comprehension in descriptive text at tenth grade of SMA N 8 Kota Jambi Academic Year 2019/2020. The researcher used a quantitative research and experimental research design as the research methodology with random sampling. The objective of this research was to find out whether there was significant effect of using sugegstopedia method on reading comprehension in descriptive text at tenth grade of SMA N 8 Kota Jambi. The sample of this research was at tenth grade of SMA N 8 Kota Jambi. The instrument of this research was a reading test. This study involved 60 students, there was consist of 30 students of control class (X MIPA 4) and 30 students of experimental class (X MIPA 2) at tenth grade of SMA N 8 Kota Jambi academic year of 2019/2020 as the object of the study and divided into two classes. Reading comprehension in descriptive text is effect after treatment suggestopedia method which is proven with student’s score higher than before treatment. The average pre-test control class 38,6 and post-test control class 53,3. Average pre-test experimental class 46 and post-test experimental class 90,8. Suggestopedia method makes learning process more interesting. The value of t-test higher than the value of t-table (20,41>2,001) based on the finding above, it can be concluded that suggestopedia method has a significant effect of reading comprehension in descriptive text at tenth grade of SMA N 8 Kota Jambi.Key Words: Suggestopedia, Reading Comprehension, Descriptive Text.